Portal Hypertension, Nodular Regenerative Hyperplasia of the Liver, and Obstructive Portal Venopathy due to Metastatic Breast Cancer. (31st July 2013) - Turk, Andrew T.; Szabolcs, Matthias J.; Lefkowitch, Jay H.
Abstract : Nodular regenerative hyperplasia (NRH) of the liver is associated with noncirrhotic portal hypertension, rheumatologic and hematologic disorders, administration of certain drugs, and other underlying conditions. This report describes a 64-year-old man with clinically presumed cirrhosis who presented to our institution with coffee-ground emesis, esophageal varices, ascites, and encephalopathy. Eleven years earlier he had been treated for breast cancer with mastectomy and chemo-radiotherapy. He died suddenly, and the autopsy showed no evidence of cirrhosis but instead demonstrated NRH with extensive emboli of recurrent breast carcinoma within the portal vein and its intrahepatic branches. Neoplastic occlusion of the portal vein as a cause of presinusoidal noncirrhotic portal hypertension has not previously been reported for metastatic breast carcinoma. This case highlights the importance of obstructive portal venopathy in the pathogenesis of NRH as well as the diagnostic difficulties that may be encountered in determining the cause of portal hypertension.